THE IMPLEMENTATION ANALYSIST OF ENTREPRENEURIAL ORIENTATION - Purba, Ilham Rizki; Suryanto, Suryanto; Kostini, Nenden (Advances in Social Sciences Research Journal, 2019)
The purpose of this study is to analyze and figure out deeply about what can entrepreneurial orientation form the competitive advantage and the company performance, also what is more dominant than entrepreneurial orientation that can shape the competitive advantage and the company performance. The method of this study is descriptive qualitative. The result of this study shows that: First, proactive is appeared by identifying a market opportunity and take care of the client relationship. The innovation is less applied with the purpose of effective and efficient. The next one is risk-taking even though with limited human resource and lack of verified product. Besides that, the competitive aggressiveness is shown by the pricing strategy but giving optimal services. The last one is autonomy with the legality of the company and poor in administration. Second, the dominant aspect of entrepreneurial orientation so that forming the attempt performance and competitive advantage is dominated by the first dimension that consists of proactive, in the second dominant aspect is competitive aggressiveness. The third aspect is the courage dimension in taking the risk and the fourth and fifth aspects are autonomy and innovative dimension.